The double-layered chemical structure in DB white dwarfs - Althaus, Leandro Gabriel (2004)
The purpose of this work is to study the structure and evolution of white dwarf stars with helium-rich atmospheres (DB) in a self-consistent way with the predictions of time-dependent element diffusion. Specifically, we have considered white dwarf models with stellar masses in the range 0.60-0.85 M * and helium envelopes with masses from 10 -2 to 10 -4 M*. Our treatment of diffusion, appropriate for multicomponent gases, includes gravitational settling and chemical and thermal diffusion. OPAL radiative opacities for arbitrary metallicity and carbon-and oxygen-rich compositions are employed. Emphasis is placed on the evolution of the diffusion-modeled double-layered chemical structure. This structure, which is characterized by a pure helium envelope atop an intermediate remnant shell rich in helium, carbon and oxygen, is expected for pulsating DB white dwarfs, assuming that they are descendants of hydrogen-deficient PG 1159 post-AGB stars. We find that, depending on the stellar mass, if DB white dwarf progenitors are formed with a helium content smaller than ≈10 -3 M*, a single-layered configuration is expected to emerge during the DB pulsation instability strip. We also explore the consequences of diffusively evolving chemical stratifications on the adiabatic pulsational properties of our DB white dwarf models. In this context, we find that the evolving shape of the chemical profile translates into a distinct behaviour of the theoretical period distribution as compared with the case in which the shape of the profile is assumed to be fixed during the evolution across the instability strip. In particular, we find that the presence of a double-layered structure causes the period spacing diagrams to exhibit mode-trapping substructures. Finally, we extend the scope of the calculations to the domain of the helium-rich carbon-contaminated DQ white dwarfs. In particular, we speculate that DQ white dwarfs with low detected carbon abundances would not be descendants of the PG 1159 stars.